Analisis Pengaruh E-Wallet Terhadap Perilaku Menabung dan Pengeluaran Konsumen di kab. takalar - Nur Alifah; Rayyani Waode (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research aims to analyze the impact of e-wallet usage on consumer saving and spending behavior in Takalar Regency. The background of this research is based on the rampant use of digital wallets (e-wallets) that offer transaction convenience but have the potential to encourage consumerist behavior. This study employs a quantitative approach using a survey method involving 100 e- wallet users residing in Takalar Regency. Data analysis is conducted using multiple linear regression to test the influence of access convenience, application features, and financial literacy on consumer saving and spending behavior. The research findings indicate that the use of e-wallets has a significant effect on increasing consumer spending, while the effect on saving behavior is moderate and depends on the individual's level of financial literacy. These findings highlight the importance of digital financial education so that the community can utilize it.